EFFECT OF HORMONAL PROTOCOLS ON BLOOD SERUM PROFILE IN POSTPARTUM ANOESTRUS BUFFALOES DURING NONBREEDING SEASON - PATIL, A D; SAHATPURE, S K; KORDE, J P; PATIL, D V (The Indian Journal of Animal Reproduction, 2022)
The study was conducted on 40 postpartum anoestrus buffaloes during non-breeding season. The selected animals were divided into 4 equal groups. Group I was treated with standard Ovsynch + CIRD protocol, Group II with CIDR alone, and Group III was administered with Ovsynch protocol alone, all with FTAI on day 10, while Group IV served as untreated control. Blood samples were collected on day 0 (initial), day 7 (day of PG inj.) and on day 10 (FTAI) of each protocol for determination of haemato-biochemical profile. The overall mean values of WBCs, RBCs, haemoglobin, plasma glucose, and serum total protein, total cholesterol, calcium and phosphorus were statistically similar on all days in all groups. The serum levels of Cu, Fe and Zn increased significantly (p<0.01) on day 7 and day 10 as compared to day 0 in treatment group, and were also higher in group I than others. The serum progesterone concentration differed significantly on all days, the level increased significantly on day 7 and dropped significantly (p<0.01) to basal level on day 10, i.e., at induced estrus/FTAI. It was concluded that except serum progesterone and trace minerals, none of the other haemato-biochemical parameters were influenced by the synchronization protocols used in anoestrus buffaloes during low breeding season.